(untitled) (Research, Society and Development, 2024)
The use of innovative pedagogical tools that enable meaningful learning are very important in teaching practice. Thus, this qualitative research aimed to evaluate the use of the Interactive Didactic Sequence (IDS) in learning about the concept of heredity in a 9th grade class at a public school in Santana do Ipanema, Alagoas. This methodology was applied in 2021, in a classroom with 15 students, using two consecutive 50-minute classes. The IDS follows three basic steps: (I) individual concept; (II) group concept; (III) general synthesis concept. After applying the methodology, we can conclude that the concept formulated by the students is close to the scientific concept, confirming that the interaction between them resulted in good learning of the concept worked on. Finally, we show that the IDS is an important methodological tool for teaching, as it encourages the student’s protagonism in the construction of knowledge, where their experiences inside and outside the school are considered. Furthermore, we highlight that the work was carried out in a pandemic scenario, which resulted in educational changes, such as smaller classes, which may have facilitated the application of IDS. However, we emphasize that IDS is an indispensable methodology, being validated by several authors in the educational field.